2014
DOI: 10.1002/jcph.256
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cobicistat boosted‐elvitegravir administered in combination with rosuvastatin

Abstract: Statins are commonly used medications by HIV-1 patients. Elvitegravir/cobicistat/emtricitabine/tenofovir DF is a single tablet regimen for the treatment of HIV. The pharmacokinetic interaction between cobicistat-boosted elvitegravir (EVG/co) and rosuvastatin was evaluated. Breast cancer resistance protein (BCRP) and organic anion transporting polypeptide (OATP) 1B1 and 1B3 inhibition were assessed in vitro. Healthy subjects (N = 12) received a single dose of rosuvastatin 10 mg alone and in combination with EVG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
(46 reference statements)
2
22
0
Order By: Relevance
“…In a recent analysis of 10 healthy subjects co-administered COBI/EVG with rosuvastatin, there was an increase in the rosuvastatin C max of89%, but only a 38% increase in the AUC, with no changes in the T max or the T 1/2 of the drug. 54 There were no differences in the pharmacokinetics of COBI or EVG when administered with rosuvastatin. 54 Based on the findings of this study, the authors recommended that rosuvastatin could be co-administered with COBI/EVG.…”
Section: Drug-drug Interactions For the Treatment Of Chronic Co-morbimentioning
confidence: 87%
See 1 more Smart Citation
“…In a recent analysis of 10 healthy subjects co-administered COBI/EVG with rosuvastatin, there was an increase in the rosuvastatin C max of89%, but only a 38% increase in the AUC, with no changes in the T max or the T 1/2 of the drug. 54 There were no differences in the pharmacokinetics of COBI or EVG when administered with rosuvastatin. 54 Based on the findings of this study, the authors recommended that rosuvastatin could be co-administered with COBI/EVG.…”
Section: Drug-drug Interactions For the Treatment Of Chronic Co-morbimentioning
confidence: 87%
“…54 There were no differences in the pharmacokinetics of COBI or EVG when administered with rosuvastatin. 54 Based on the findings of this study, the authors recommended that rosuvastatin could be co-administered with COBI/EVG.…”
Section: Drug-drug Interactions For the Treatment Of Chronic Co-morbimentioning
confidence: 87%
“…The combination of cobicistat with elvitegravir had only a modest effect on rosuvastatin exposure that was not clinically significant, allowing this combination to be used without dose adjustment [45] ": Increase; #: Decrease; AUC tau /AUC last /AUC inf : Area under the concentration-time curve to the end of the dosing period/to the last measurable concentration/to infinite time; C max : Maximum plasma concentration; C tau or C min : Plasma concentration at the end of the dosing period or minimum plasma concentration; FDC: Fixed-dose combination; HMG: 3-hydroxy-3-methyl-glutaryl; TDF: Tenofovir disoproxil fumarate.…”
Section: Darunavir/cobicistat Fdc Clinical Development Programmentioning
confidence: 97%
“…Cobicistat increased digoxin maximum plasma concentration (C max ) by 41% and exposure (area under the plasma concentrationtime curve [AUC]) by 20% [44]. The combination of cobicistat with elvitegravir had only a modest effect on rosuvastatin exposure that was not clinically significant, allowing this combination to be used without dose adjustment [45]. Similarly, drug-drug interaction studies of cobicistat and elvitegravir combined with opioids showed no clinically significant effect on methadone, buprenorphine/naloxone or cobicistat [46,47].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…It is possible that EVG has slower uptake kinetics in macrophages than MGBG. Cobicistat, a potent inhibitor of cytochrome P450 3A enzymes and intestinal transport proteins, has been used together with EVG to enhance overall drug absorption in the clinical settings (68,69).…”
Section: Figmentioning
confidence: 99%